PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP FINANCIAL DISTRESS PERUSAHAAN DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Infrastruktur dan Energi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Jericho Raditya Anugrah Putra; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on financial distress with firm value as a moderating variable in infrastructure and energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using a quantitative approach and secondary data from annual reports, sustainability reports, and Bloomberg ESG Scores, 27 companies (81 observations) were analyzed through moderated regression analysis with IBM SPSS 27. The results indicate that ESG has no significant effect on financial distress, as the benefits of ESG practices tend to be long-term and may not immediately reflect a firm’s financial condition. However, firm value significantly moderates this relationship, where higher firm value weakens the negative impact of ESG on the Altman Z-Score, suggesting that financially strong firms can better absorb ESG-related costs and maintain stability.